In vivo effect of photodynamic therapy on periodontal bone loss in dental furcations - Almeida, Juliano Milanezi de [UNESP]; Theodoro, Letícia Helena [UNESP]; Bosco, Álvaro Francisco [UNESP]; Nagata, Maria José Hitomi [UNESP]; Oshiiwa, Marie; Garcia, Valdir Gouveia [UNESP] (Amer Acad Periodontology, 2008)
Background: The purpose of this study was to histometrically evaluate the influence of photodynamic therapy on bone loss in furcation areas in rats with experimentally induced periodontal disease.Methods: Ligatures were placed on the first mandibular molar in rats. Then the animals were divided into four groups: control group = no treatment; methylene blue group (MB) = treated topically with methylene blue (100 mu g/ml); laser group (LLLT) = treated with low-level laser therapy; and photodynamic therapy group (PDT) = treated topically with MB followed by LLLT (4.5 J/cm(2)). Rats from all groups were sacrificed at 7, 15, or 30 days postoperatively. The area of bone loss in the furcation region of the first molar was histometrically analyzed. Data were analyzed statistically (analysis of variance and Bonferroni tests; P<0.05).Results: The PDT group demonstrated less bone loss compared to the other groups at 7 days (1.986 +/- 0.417 mm(2)); at 15 days, the PDT (1.641 +/- 0.115 mm(2)) and MB groups (1.991 +/- 0.294 mm(2)) demonstrated less bone loss compared to the control (4.062 +/- 0.416 mm(2)) and LLLT (2.641 +/- 0.849 mm(2)) groups.Conclusion: Within the parameters used in this study, PDT may be an effective alternative for control of bone loss in furcation areas in periodontitis.
Keywords: bone loss; furcation defects; laser; periodontitis; photodynamic therapy